An investigation of software effort phase distribution using compositional data analysis - Chatzipetrou, Panagiota; Papatheocharous, Efi; Angelis, Lefteris; Andreou, Andreas S. (My University, 2012)
One of the most significant problems faced by project managers is to effectively distribute the project resources and effort among the various project activities. Most importantly, project success depends on how well, or how balanced, the work effort is distributed among the project phases. This paper aims to obtain useful information regarding the correlation of the composition of effort attributed in phases for around 1,500 software projects of the ISBSG R11 database based on a promising statistical method called Compositional Data Analysis (CoDA). The motivation for applying this analysis is the observation that certain types of project data (effort distributions and attributes) do not relate in a direct way but present a spurious correlation. Effort distribution is compared to the project life-cycle activities, organization type, language type, function points and other prime project attributes. The findings are beneficial for building a basis for software cost estimation and improving future empirical software studies. 2012 IEEE.
Keywords: Compositional data; Effort analysis; Function point; Phase distribution; Prime projects; Project activities; Project data; Project managers; Project phasis; Project resources; Project success; Software cost estimations; Software effort; Software project; Engineering; Industrial engineering; Software engineering